Hydrated lime promoted the polysaccharide content and affected the transcriptomes of Lentinula edodes during brown film formation - Li, Yan; Wang, Hongcheng; Zhang, Ying; Xiang, Quanju; Chen, Qiang; Yu, Xiumei; Zhang, Lingzi; Peng, Weihong; Penttinen, Petri; Gu, Yunfu (Frontiers in Microbiology, 2023)
Brown film formation, a unique developmental stage in the life cycle of Lentinula edodes, is essential for the subsequent development of fruiting bodies in L. edodes cultivation. The pH of mushroom growth substrates are usually adjusted with hydrated lime, yet the effects of hydrated lime on cultivating L. edodes and the molecular mechanisms associated with the effects have not been studied systemically. We cultivated L. edodes on substrates supplemented with 0% (CK), 1% (T1), 3% (T2) and 5% (T3) hydrated lime (Ca (OH)2), and applied transcriptomics and qRT-PCR to study gene expression on the brown film formation stage. Hydrated lime increased polysaccharide contents in L. edodes, especially in T2, where the 5.3% polysaccharide content was approximately 1.5 times higher than in the CK. The addition of hydrated lime in the substrate promoted laccase, lignin peroxidase and manganese peroxidase activities, implying that hydrated lime improved the ability of L. edodes to decompose lignin and provide nutrition for its growth and development. Among the annotated 9,913 genes, compared to the control, 47 genes were up-regulated and 52 genes down-regulated in T1; 73 genes were up-regulated and 44 were down-regulated in T2; and 125 genes were up-regulated and 65 genes were down-regulated in T3. Differentially expressed genes (DEGs) were enriched in the amino acid metabolism, lipid metabolism and carbohydrate metabolism related pathways. The carbohydrate-active enzyme genes up-regulated in the hydrated lime treatments were mostly glycosyl hydrolase genes. The results will facilitate future optimization of L. edodes cultivation techniques and possibly shortening the production cycle.